THE INFLUENCE OF MARINE PORT SERVICE WORK DISTRIBUTION AT THE TERMINAL ON FREIGHT STATION WORK PERFORMANCE - S. I. Muzykina; G. I. Peresta; I. L. Zhuravelj; V. V. Zhuravelj (Nauka ta progres transportu, 2010)
In the article the urgency of rational distribution at the terminal of sorting work with the local cars on selecting them by the destinations of freight fronts of marine trade port is conditioned. The results of analysis of the basic operation indices of the terminal freight station and marshalling yard are presented.